Tourism sector assessment, strategy, and road map for Cambodia, Lao PDR, Myanmar, and Vietnam (2016-2018). (Country sector and thematic assessments., 2017)
This report documents tourism sector investment priorities of the Asian Development Bank (ADB) and the governments of Cambodia, the Lao People Democratic Republic, Myanmar, and Viet Nam. It highlights sector performance, priority development constraints, government plans and strategies, past ADB support and experience, and other development partner support.